Direct Numerical Simulation of Multiple Particles Sedimentation at an Intermediate Reynolds Number (Communications in Computational Physics, 2014)
In this work the previously developed Lattice Boltzmann-Direct Forcing/Fictitious Domain (LB-DF/FD) method is adopted to simulate the sedimentation ofeight circular particles under gravity at an intermediate Reynolds number of about248. The particle clustering and the resulting Drafting-Kissing-Tumbling (DKT) motion which takes place for the first time are explored. The effects of initial particle-particle gap on the DKT motion are found significant. In addition, the trajectories ofparticles are presented under different initial particle-particle gaps, which display totally three kinds of falling patterns provided that no DKT motion takes place, i.e. theconcave-down shape, the shape of letter "M" and "in-line" shape. Furthermore, thelateral and vertical hydrodynamic forces on the particles are investigated. It has beenfound that the value of Strouhal number for all particles is the same which is about0.157 when initial particle-particle gap is relatively large. The wall effects on fallingpatterns and particle expansions are examined in the final.